Constitutionalism in global constitutionalisation - O'Donoghue, Aoife 1981- (Cambridge Univ. Press, 2014)
"Constitutionalism offers a governance order a set of normative values including, amongst others, the rule of law, divisions of power and democratic legitimacy. These normative values regulate the relationship between constituent and constituted power holders. Such normative constitutional legal orders are commonplace in domestic systems but the global constitutionalisation debate seeks to identify a constitutional narrative beyond the state. This book considers the manner in which the global constitutionalisation debate has neglected constitutionalism within its proposals. It examines the role normative constitutionalism plays within a constitutionalisation process, and considers the use of community at both the domestic and global governance levels to identify the holders of constituent and constituted power within a constitutional order. In doing so this analysis offers an alternative narrative for global constitutionalisation based within normative constitutionalism"..